A new genus and two new species of melicharid mites (Acari: Mesostigmata) associated with wood-decaying fungi and mycophagous erotylid beetles (Coleoptera: Erotylidae) in Europe - Mašán, Peter; Joharchi, Omid; Abramov, Vladimir V. (Zootaxa, 2021)
We describe a new genus in the mite family Melicharidae, Mycomelichares Mašán & Joharchi gen. nov., to accommodate two new species, Mycomelichares polypori Mašán & Joharchi sp. nov. and Mycomelichares reductus Mašán & Joharchi sp. nov. on the basis of specimens collected on wood-decaying fungi and/or mycophagous beetles of the genera Triplax Herbst and Tritoma Fabricius (Coleoptera: Erotylidae) in Slovakia and European part of Russia, respectively. Moreover, two previously described Proctolaelaps species—P. cyllodi Samšiňák, 1960 and P. slovacus Mašán, 1998 are transferred to the newly established genus. The new genus is characterized by specific characters in tritosternum (enlarged and brush-shaped, having their laciniae thickened, basaly fused and distally densely pilose), chelicerae (slightly dish-shaped digits with long, narrow and sharp denticles), ventral hypostome (setae h1 enlarged, thickened and distally flattened), setation (tendency towards placement of R series setae on soft integument, and reduction of some setae on idiosoma and legs), and unusual ecological specialisation on fungal substrates. Mycomelichares polypori sp. nov. is adapted to the life in sporophores of the basidiomycete bracket fungus, Polyporus squamosus (Polyporaceae). Mites of this species can be abundantly found on the lower fertile surface of the fungus, including large spore-bearing pores. Furthermore, keys to the melicharid genera reported from Palaearct, and the species of the genus are provided.